2017
DOI: 10.1007/s40520-017-0767-y
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of advanced gastric cancer with negative or only perigastric lymph node metastasis in elderly patients

Abstract: In the elderly patients, LN metastasis in advanced gastric cancer of ≤40 mm in diameter was limited to be within the perigastric area. Gastrectomy with only perigastric LN dissection may be adopted in these patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 30 publications
0
1
0
Order By: Relevance
“…45 LN s were metastatic and 37 LN s were pathologically inflammatory. The cases included gastrooesophageal junction carcinoma: Siewert II (8) and Siewert III (4), gastric body carcinoma (9), gastric antrum carcinoma (12) according to the location of gastric tumors; T1N0 (6), T1N1 (10), T1N2 (13) and T1N3 (4) according to post-operative T and N staging of gastric cancer; AS well, well-differentiated Perfusion CT parameters result Figure 3 demonstrated that metastatic LN and T1 gastric cancer had high blood perfusion and permeability; Figure 4 demonstrated that inflammatory LN s and T1 gastric cancer had moderate blood perfusion and permeability. The average BF and PS values, short axis diameters of metastatic and inflammatory LN s were detailed in Table 1.…”
Section: Clinicopathological Resultsmentioning
confidence: 99%
“…45 LN s were metastatic and 37 LN s were pathologically inflammatory. The cases included gastrooesophageal junction carcinoma: Siewert II (8) and Siewert III (4), gastric body carcinoma (9), gastric antrum carcinoma (12) according to the location of gastric tumors; T1N0 (6), T1N1 (10), T1N2 (13) and T1N3 (4) according to post-operative T and N staging of gastric cancer; AS well, well-differentiated Perfusion CT parameters result Figure 3 demonstrated that metastatic LN and T1 gastric cancer had high blood perfusion and permeability; Figure 4 demonstrated that inflammatory LN s and T1 gastric cancer had moderate blood perfusion and permeability. The average BF and PS values, short axis diameters of metastatic and inflammatory LN s were detailed in Table 1.…”
Section: Clinicopathological Resultsmentioning
confidence: 99%